2019
DOI: 10.1001/jamaoncol.2019.1467
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance Therapy With Panitumumab Alone vs Panitumumab Plus Fluorouracil-Leucovorin in Patients With RAS Wild-Type Metastatic Colorectal Cancer

Abstract: IMPORTANCE Few studies are available on the role of maintenance strategies after induction treatment regimens based on anti-epidermal growth factor receptors, and the optimal regimen for an anti-epidermal growth factor receptors-based maintenance treatment in patients with RAS wild-type metastatic colorectal cancer is still to be defined. OBJECTIVETo determine whether maintenance therapy with single-agent panitumumab was noninferior to panitumumab plus fluorouracil and leucovorin after a 4-month induction trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 29 publications
3
91
1
1
Order By: Relevance
“…Consistent with the literature, 13 , 19 MSI-high status was associated with poor PFS outcome at the univariable analysis, although the number of MSI-high occurrences in this data set was quite small (only five patients) and did not allow us to properly assess its independent prognostic role. The type of maintenance treatment retained its value in terms of PFS but not OS; this result has been already reported 11 and may be due to the low number of OS events at the time of data cutoff and to the underpowered sample size.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Consistent with the literature, 13 , 19 MSI-high status was associated with poor PFS outcome at the univariable analysis, although the number of MSI-high occurrences in this data set was quite small (only five patients) and did not allow us to properly assess its independent prognostic role. The type of maintenance treatment retained its value in terms of PFS but not OS; this result has been already reported 11 and may be due to the low number of OS events at the time of data cutoff and to the underpowered sample size.…”
Section: Discussionmentioning
confidence: 51%
“…The Valentino study was a multicenter, randomized, open-label, phase II trial that investigated the progression-free survival (PFS) noninferiority of maintenance with single-agent panitumumab (arm B) versus panitumumab plus FU plus LV (arm A) after an induction treatment with panitumumab plus FOLFOX-4 in patients with RAS wild-type mCRC. 11 The trial enrolled 229 patients (arm A, n = 117; arm B, n =112) and showed that maintenance with single-agent panitumumab is inferior to panitumumab plus FU/LV in terms of PFS.…”
Section: Methodsmentioning
confidence: 99%
“…To date, the therapeutic algorithm for the choice of the best treatment for mCRC patients has been characterized by a negative selection, restricting the treatment with anti-EGFR agents to patients with wild-type RAS and BRAF mCRC [109,110]. Moving forward the era of positive selection in mCRC, results from the phase III BEACON trial, which randomized 665 pretreated patients with BRAF V600E mutant mCRC to receive triplet therapy (encorafenib, binimetinib and cetuximab), doublet therapy (encorafenib and cetuximab), or the investigator’s choice of irinotecan or FOLFIRI and cetuximab, showed an impressive median overall survival of 9 months (95% confidence interval (CI): 8, 11.4) for the triplet targeted therapy compared to 5.4 months (95% CI: 4.8, 6.6) for standard therapy (hazard ratio (HR) 0.52; 95% CI: 0.39, 0.7, p < 0.0001) and an ORR of 26% (95% CI: 18, 35) for the triplet targeted therapy compared to 2% (95% CI: 0,7, p < 0.0001) for standard therapy [111,112].…”
Section: Discussionmentioning
confidence: 99%
“…These results have been confirmed in subsequent studies of firstline treatment of molecularly selected mCRC with chemotherapy plus anti-EGFR MoAbs, such as the VALENTINO trial that investigated the combination of FOLFOX plus panitumumab. 24 We conducted a post hoc analysis for assessing the feasibility and the efficacy of FOLFIRI plus cetuximab in elderly patients who were enrolled in the CAPRI-GOIM clinical trial, considering that the majority of mCRC cases are diagnosed in the elderly. 25 Phase II and III studies have shown the safety and clinical activity of bevacizumab in combination with fluoropyrimidine-based regimens in elderly patients with mCRC who are unfit for chemotherapy doublets.…”
Section: Correlation Between the Efficacy Of First-line Treatment Witmentioning
confidence: 99%